Integrative proteome and metabolome analyses reveal molecular basis of the tail resorption during the metamorphic climax of Nanorana pleskei - Zhang, Tao; Jia, Lun; Li, Xinying; Niu, Zhiyi; Zhang, Siping; Dong, Weijun; Peng, Liang; Ma, Miaojun; Wang, Huihui; Tang, Xiaolong; Chen, Qiang (Frontiers in Cell and Developmental Biology, 2024)
During the metamorphosis of anuran amphibians, the tail resorption process is a necessary and crucial change. One subject that has received relatively little or no attention is the expression patterns of proteins and metabolites in the different tail portions during metamorphosis, especially in highland amphibians. The mechanisms of tail resorption in three portions (the tip, middle and root) of the tail were investigated in Nanorana pleskei G43 tadpole based on two omics (proteomic and metabolomic). Integrin αVβ3 was found to be high expressed in the distal portion of the tail, which could improve the sensitiveness to thyroid hormones in the distal portion of the tail. Muscle regression displayed a spatial pattern with stronger regression in distal and weaker one in proximal portion. Probably, this stronger regression was mainly performed by the proteases of proteasome from the active translation by ribosomes. The suicide model and murder model coexisted in the tail resorption. Meanwhile, fatty acids, amino acids, pyrimidine, and purine which derived from the breakdown of tissues can be used as building blocks or energy source for successful metamorphosis. Our data improved a better comprehension of the tail resorption mechanisms underlying the metamorphism of N. pleskei tadpole through identifying important participating proteins and metabolites.